Fear of Covid-19 as a mediator between neuroticism and health anxiety among university students in Qatar - Adawi, Taha R.; Elsherbiny, Atef Mosaad; Elbahnsawy, Ahmed Kamal Abdelwahab; Bataineh, Osamah Mohammad Falah (Dirasat: Educational Sciences, 2023)
Objectives: This research aims at identifying levels of fear of Covid-19, neuroticism, and health anxiety among university students in Qatar. In addition, it aims to identifying gender differences in fear of Covid-19, neuroticism, and health anxiety, and testing whether fear of Covid-19 mediates the relationship between neuroticism and health anxiety. Methods: This research utilized a descriptive correlational approach. The research sample included 236 participants from colleges of Arts, Education, and Engineering (age range= 18-46, M= 24.98, SD= 6.24). Results: Results show that levels of Fear of Covid-19, neuroticism, and health anxiety range from moderate to extremely low (32.15-59.24 %). No gender differences were found and fear of Covid-19 mediated the relationship between neuroticism and health anxiety. Conclusions: Based on the results. It is recommended to do further research on the psychological impacts of Covid 19 and its relationship to other psycho-social variables.